The Relative Efficiency of the Real Sector versus the Financial Sector of the Colombian Economy - Rodriguez Lozano, Gloria Isabel; Sarmiento Muñoz, Michael Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this research is to compare the companies of the real sector of the economy and the entities of the Colombian financial sector for the year 2014, in terms of relative efficiency, through the application of the Data Envelopment Analysis (DEA) methodology. For a country like Colombia, belonging to the emerging economies, it is important to conduct this study to determine how far these two sectors are efficient or inefficient, given the importance they have in generating development and reducing social inequalities. We take as source of information the Superintendencia de Sociedades and the Superintendencia Financiera. 26,799 companies in the real sector and financial sector entities 254 were analyzed resulting in better indicators for the financial sector and within this, the insurance industry stands. However it is necessary that these two sectors improve their performance to the extent that only 2.6% of studied companies and entities are efficient.